Perancangan Alat Bantu untuk Liquid Container Berdasarkan Penilaian Rapid Entire Body Assessment dan Washington State Checklist - Risya Rahmasari Kosasih; Sri Martini; Mira Rahayu (Universitas Serang Raya, 2019)
The problem in this research is the use of liquid containers, which use as bulk cosmetic containers, which will be move from the WIP room to the product packaging room. Based on these transfer activities, there was a risk of exposure to Musculoskeletal Disorders (MSDs), which were analyzed using Rapid Entire Body Assessment (REBA) and Washington State Checklist (WSC). This study aims to design a tool for a more ergonomic liquid container to reduce the impact of MSDs on workers. Redesigning this tool uses the concept of Reverse Engineering. The design of the new liquid container transporter simulation can reduce REBA score with a WSC value of low-risk category for MSDs exposure based on the overall work environment category.